Using Referenda to Improve Targeting and Decrease Costs of Conditional Cash Transfers - Alix-Garcia, Jennifer M.; Sims, Katharine R.E.; Phaneuf, Daniel J. (World Bank, Washington, DC, 2019)
Cost-effective allocation of conditional cash transfers (CCT) requires identifying recipients with low opportunity costs who might change behavior. This paper develops a low-cost approach for improving program implementation by using a stated preference, referendum-style survey question to calculate willingness to accept (WTA) for CCT contracts. This is illustrated in the context of Mexico's Payments for Ecosystem Services Program, with the paper finding that the estimated social cost based on WTA is substantially lower than actual payments. Simulation of three geographic targeting approaches shows that joint selection using deforestation risk and WTA could increase program impact under the same budget. The paper also simulates modified payment schedules based on predicted WTA and demonstrates that these could reduce program cost.